Coral Reef Coupling to the Atmospheric Boundary Layer Through Exchanges of Heat, Moisture, and Momentum: Case Studies From Tropical and Desert Fringing Coral Reefs - McGowan, Hamish; Lensky, Nadav G.; Abir, Shai; Saunders, Melissa (Frontiers in Marine Science, 2022)
Coral reefs represent abrupt changes in surface roughness, temperature, and humidity in oceanic and coastal locations. This leads to formation of internal atmospheric boundary layers that grow vertically in response to turbulent mixing which conveys changes in surface properties into the prevailing wind. As a result, coral reefs under favourable conditions couple to the overlying atmosphere. Here we present rare observations of coral reef – atmospheric interactions during summer monsoon conditions on the Great Barrier Reef, Australia, and a desert fringing coral reef in the Gulf of Eilat, Israel. We show that in the hyper-arid location of the Gulf of Eilat where air temperatures are greater than water temperatures, a stable atmospheric boundary inhibits coupling of the reef to the atmosphere. In contrast, under monsoon conditions on the Great Barrier Reef, the coral reef is shown to couple to the overlying atmosphere leading to the formation of a convective internal boundary layer in which convective exchange of heat and moisture influences cloud and possibly precipitation. We conclude that understanding these processes is essential for determining the role of coral reefs in coastal meteorology, and whether through coupling with the overlying atmosphere coral reefs may regulate their meteorology by triggering formation of cloud and/or vertical exchange on aerosols and their precursor gases such as Dimethyl sulphide.